Pola Pemukiman Etnis Tionghoa Di Kampung Peunayong - Sri Ahmat Helmisyah; Rifki Rosyad (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2021)
This study focuses on the existence of ethnic Chinese in Peunayong Village, Banda Aceh City. Ethnic Chinese have been associated with Indonesia hundreds of years ago. Ethnic Chinese came to the archipelago to establish cooperation in terms of friendship and also in trade. The relationship between Indonesia and the Chinese ethnic group continued, especially in the Kingdom of Aceh until the Dutch East Indies colonial rule. The article will discuss how the life of the Chinese ethnic group during the Dutch East Indies colonial era until today. The aim is to find out about the existence of ethnic Chinese in Peunayong Village and the relationship between Acehnese ethnic and Chinese in that place. This paper uses secondary research methods, namely research that utilizes secondary data, existing data. Secondary data can be in the form of research results data, it can also be documentary data on institutional administration. It is hoped that knowing the existence of the Chinese ethnic group can make a difference in society and not cause conflicts.